Dampak Teknologi sebagai Dasar Pengembangan Media Pembelajaran terhadap Prestasi Siswa Ditinjau dari Teori Belajar Humanistik - Ni Putu Noviarini; Ni Ketut Suarni; I Gede Margunayasa (Ideguru: Jurnal Karya Ilmiah Guru, 2024)
The development of information and communication technology has changed the educational landscape by providing a solid foundation for the development of innovative learning media. This article aims to analyze the impact of technology as a basis for developing learning media on student achievement, by referring to humanistic learning theory. The research method used is library research, which involves collecting data from various relevant literature sources. The results of the analysis show that the use of technology in learning has provided significant benefits in improving student achievement. Technology-based learning media, such as interactive multimedia and online learning, facilitate a more engaging and relevant learning experience for students. In the context of humanistic learning theory, technology can help create a more personalized learning environment, where students have more control over their learning process. Thus, this article underscores the importance of utilizing technology as a tool to improve student achievement through a more humane and individually focused approach to learning.